Chang of Body Composition by Thai Boxing Training Program in Female Age 20-35 Years - Buenaedama, Alliats; Tengku Sulaiman, Rajasyed; Choeychom, Kongkiat (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were to study and compare the effect of Thai boxing training program on body composition changing of female. The samples used in the research was female 20-35 years of age who participated in the Phuket Municipality exercise for health project. The 30 samples of this study were chosen by the simple random sampling method. The instrument used in this research are skin fold caliper, Jackson and Pollock body density equation as well as Siri percent body fat equation. The statistics for the data analysis were mean, standard deviation, One-way ANOVA with Repeated and the multiple comparison using the Bonferroni’s Test. The significance level was set at 0.05. The results showed that the percent body fat mean scores of female 20-35 year of age before training was rated 37.54 percent, and the standard deviation was rated at 2.50. The percent body fat mean scores after 4th week of training was rated 37.25 percent, and the standard deviation was rated at 2.49. The percent body fat mean scores after 8th week of training was rate 35.75 times, and the standard deviation was rated at 1.18. However, this study also found that, there were significant difference of the percent body fat mean scores between before and after 8th week of training and after 4th and 8th week of training at the 0.05 level. While the percent body fat mean scores between before and and after 4th week of training was no significant difference.